Exploring the Perceived Influence of Mobile Learning on Environmental Awareness and Literacy among Students of Adekunle Ajasin University, Akungba-Akoko, Nigeria - Olatumile, Adekunle (NIU Journal of Social Sciences, 2019)
One of the wonders of the twenty-first century is the revolution of Information Communication Technologies (ICTs), The mobile device which is used among people has the potential to support learning.  Mobile learning is creating more and more space for informal learning; it becomes important to understand how the boundaries are shifting and what the implications are. The use of mobile phones in creating environmental awareness and inculcating pro-environmental behaviour have not received the necessary and adequate attention in the quest of global effort geared towards solving the myriad and life threatening environmental problems facing humanity in the 21 st century. The paper ascertains students usage of mobile phone for learning; opportunities that mobile phone provide in environmental awareness and learning; the effectiveness of mobile phone on environmental awareness and learning; the usefulness of mobile phone for environmental awareness and learning; how mobile phone enhances environmental awareness and learning. Two hundred copies of questionnaire were administered and sorted; one hundred and forty six that were deemed to have been well filled were used for the study. Findings of the study revealed that students use mobile phones to perform a variety of educational tasks, are useful for creating environmental awareness, are effective learning aid for students with regard to environmental issues and are easy for creating environmental awareness. The study comes up with a framework for designing mobile learning for environmental literacy. Keywords: Information Communication Technologies; Environmental awareness; mobile phones; Learning; Environmental literacy.